Editorial: Journal Development, Scholar Development and Quality - Eureta Rosenberg (Environmental Association of Southern Africa, 2017)
Recently, the 33-year journey of the Southern African Journal of Environmental Education (SAJEE) was the subject of reflection during an Open Access Publishing week convened by Rhodes University Library Services. Two former and current editors-in-chief shared the SAJEE's story of publishing 'from the margins into the centre'. In the early 1990s, the Journal was mailed to the Environmental Education Association of Southern Africa (EEASA) membership from the foyer of the Rhodes Education Department (which had the floor space for stuffing and stacking A4 envelopes). In the first decade of this century, the Journal arrived at a symbolic 'centre' with digital distribution, first on the EEASA website and then from the Open Access platform provided by African Journals Online (AJOL). The digital move was vital for sustained and increased distribution in a time of shrinking budgets and growing costs. The results, shared with the EEASA Council earlier this year, were nothing short of spectacular: In March 2017, the SAJEE received more than 1 250 article downloads (www.ajol.info/index.php/sajee), and the number of downloads have stayed above 500 each month subsequently (Figure 1). Views and downloads are recorded around the world including vitally, in English-speaking Africa, with a high percentage in the entire Southern African Development Community (SADC) region Online publishing is, however, a double-edged sword. It gives greater access to research findings and scholarly ideas and reduces the cost of reaching readers, educators, policymakers and fellow researchers. But, precisely because the limitations of physical publishing - printing, paper and postage - are removed, online publishing also has a dark side: the potential for poorer quality. It is easier to publish more papers and to cut corners in the processes that maintain the rigour of academic publishing, which are the very foundation of the reputation and value of scholarly work. Thus, at a conference on The Future of Scholarly Publishing in Stellenbosch, in October 2017, a contributor to a forthcoming report on scholarly publishing by the Academy of Sciences in South Africa (ASSAf), Prof. Johann Mouton, spoke of a 'crisis of quality'.